Do Air-Traffic passengers make rational decisions when purchasing ancillary services? - A behavioural economic analysis - - Strey,Steve (2018)
The sale of ancillary services has become an important source of revenue for modern airlines. However, no research has yet been done on the purchasing behaviour of air-traffic passengers. Therefore, the aim of this empirical study is to analyse if passengers behave rationally when purchasing ancillary services or if their preferences can be manipulated by framing effects. To answer the research question, we test various framing effects for their significance by utilizing cross-section data and different evaluation methods. The results indicate that endowment, power of the free, bundle pricing, flight distance and the passengers’ age and income have a strong impact on the passengers’ willingness to pay for ancillary services. A weak influence can be found for loss aversion and the decoy effect.
Keywords: Ancillary Services; Airline; Framing Effect; Purchasing Behaviour